(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
Measurements of heat affected zone width for multi high carbon steel joint in case of single and double pass arc welded have been studied. These measurements are carried out in accompanying of hardness and microstructural observations. Knowing that, high carbon steel has a poor weld ability and most of welding processes are carried out for repairing components. It is found that a preheating was a very important parameter in identifying the width of heat-affected zone. Preheating the joint at 450°C was found to gives less width heat affected zone (i.e.5.93mm) in the case of single pass welding practices. While, in the case of double pass welding, the heat affected zone becomes wider because the excessive heating during welding cycle. The double pass welding has coarsening the structure of first pass. Microscopic observations indicated that the structure of HAZ of high carbon steel was mainly lath martensite (ML) under the condition of lower weld heat input.